Evaluating the sectoral competitiveness and welfare effects in SACU economies under the AfCFTA framework - Kubhayi, Vusimani Prian (Rhodes University, 2026)
As the AfCFTA gains attention as an engine to drive intra-African trade, this study aims to evaluate sectoral competitiveness and welfare effects while highlighting the unavoidable short-term fiscal revenue losses. A CGE model has been employed to evaluate the sectoral competitiveness and welfare impacts of a 100% AfCFTA tariff removal on SACU countries, with a focus on the agricultural and manufacturing sectors. The analysis draws on 2019 data, which was chosen to minimise the disruption caused by the effects of COVID-19. The findings show that South Africa and Namibia incurred the most significant fiscal revenue losses of –$66.85 million and –$28.06 million, respectively. Despite Eswatini's high dependence on tariff revenue, accounting for +36.2% after Lesotho (+46.80%), it is the only country with a positive net welfare gain of +$3.58 million, with manufacturing showing strong competitiveness. Botswana (+14.75%) is the second highest with respect to income growth after Eswatini (+19.43%), whereas Namibia observed the most significant income decline (-28.10%). The top two countries in wage growth are South Africa and Namibia, which increased by +13.65% and +6.56%, respectively, while Botswana recorded the most significant wage decline of -38.67%. Botswana is the only country with increased consumption in both sectors and the only country showing agriculture as a capital-intensive sector. Overall, most benefits accrued by SACU countries emanate from the manufacturing sector, which has export competitiveness potential, especially in South Africa, Namibia, and Eswatini, while agriculture is competitive in Botswana and Namibia.
Keywords: Uncatalogued